The Influence of Green accounting, Sustainability Report Disclosure and Environmental Performance on Firm Value - Azzahra, Amalia Cahya; Damayanti, Damayanti; Dewi, Anita Kusuma (Goodwood Akuntansi dan Auditing Reviu, 2025)
Purpose: This study aims to examine the effect of green accounting, sustainability report disclosure, and environmental performance on firm value of companies listed on the Indonesia Stock Exchange (IDX) and registered as PROPER participants during 2019-2023. Methodology/approach: a quantitative approach was employed using secondary data from annual reports, financial statements, and sustainability reports of the sample companies. Purposive sampling was applied, resulting in 30 companies that met the criteria. Data analysis was conducted through multiple linear regression with SPSS version 25. Results/findings: The results indicate that green accounting and environmental performance have a positive and significant effect on firm value, while sustainability report disclosure shows a negative significant effect. Simultaneously, the three independent variables significantly affect firm value with an adjusted R 2 of 18.8%, suggesting that other variables outside the model explain the remaining variation. Conclusions : The study concludes that environmentally based practices such as green accounting and strong environmental performance strengthen legitimacy and investor confidence. However, sustainability report disclosure has not yet been perceived as value-added information in the Indonesian context. Limitations: The study is limited by the possibility that the effects of sustainability practices may not be visible in the short term. Companies are advised to improve environmental standards and separate environmental costs from CSR to enhance transparency. Contribution: This research contributes to the accounting and sustainability literature by providing empirical evidence on the role of environmental practices in firm value. The findings are useful for companies, regulators, policymakers in strengthening sustainability practices and improving long-term corporate reputation.